The impact of positive margins and crypt involvement in excisional procedures of the cervix on recurrence rates of premalignant diseases of the cervix - Addae, Haleema (Department of Obstetrics and Gynaecology, 2021)
BACKGROUND Recurrent disease after cervical excisional procedures has been linked to many factors. We aim to determine if positive margins and crypt involvement increased the rate of recurrence of premalignant disease in patients who had excisional procedures. METHODS In this retrospective review of the colposcopy database, patient records and pathology database, women who had cervical excisional procedures at the Groote Schuur Hospital colposcopy clinic in 2010 were followed up until 2015. Recurrence was based on high grade cytology or histology at follow up. Chi-square tests were used to compare recurrence rates. RESULTS Two hundred and seventy women were included in the final analysis. 130 women had CIN 3 and 94 had CIN 2 at the excisional procedure. Eighty five (31.5%) had endo-margin involvement, 46 (17%) had ecto-margin involvement, and 24 (8.9%) had dual margin involvement. Two hundred and thirteen (79.2%) had crypt involvement. Recurrence occurred in 30 (19.4%) of the 155 patients we had follow up data on. Of those that recurred, 19 (P<0.001) had positive endo-margin involvement, 10 (P=0.007) had ecto-margin involvement, 9 (P< <0.001) had dual margin involvement, and 28 (P=0.058) had crypt involvement. 155 women (43%) were lost to follow-up CONCLUSION Positive margins at excisional procedure of the cervix have a statistically significant increased risk of recurrence of pre-malignant disease. There was a trend towards recurrence of disease in those who have crypt involvement. In limited resource setting follow up protocols can be adjusted so that women without margin involvement can be seen at longer intervals.